A novel bacteriocin BMP11 and its antibacterial mechanism on cell envelope of Listeria monocytogenes and Cronobacter sakazakii. (September 2018) - Yi, Lanhua; Li, Xin; Luo, Lingli; Lu, Yingying; Yan, Hong; Qiao, Zhu; Lü, Xin
Abstract: Listeria monocytogenes and Cronobacter sakazakii are notorious pathogens involved in numerous foodborne outbreaks after ingested contaminated food. Bacteriocins are natural food preservatives, some of which have antimicrobial activity comparable with antibiotics. In this study, a plasmid encoded novel bacteriocin BMP11 produced by Lactobacillus crustorum MN047 was innovatively identified by combining complete genome and LC-MS/MS. The BMP11 was found to have rich α-helix conformation after prediction. Moreover, the antimicrobial activity of BMP11 was verified after its heterologous expression in E. coli with 1280 and 640 AU/mL against L. monocytogenes and C. sakazakii, respectively. After purification by anion-exchange chromatography and HPLC, BMP11 had MIC values of 0.3–38.4 μg/mL against tested foodborne pathogens. Further, it was found that BMP11 had bactericidal action mode with concomitant cell lysis to pathogens by growth curve and time-kill kinetics. The results of scanning electron microscope (SEM) and transmission electron microscope (TEM) indicated that BMP11 destroyed the integrity of cell envelope of pathogens with cell wall perforation and cell membrane permeabilization. The destruction of cell envelope integrity was further verified by propidium iodide (PI) uptake and lactic dehydrogenase (LDH) release. BMP11 increased inner-membrane permeability of C. sakazakii in a concentration-dependent manner. Meanwhile, BMP11 exhibited antibiofilm formation activity. In addition, BMP11 inhibited the growth of L. monocytogenes in milk. Therefore, BMP11 had promising potential as antimicrobial to control foodborne pathogens in dairy products. Highlights: A novel bacteriocin BMP11 was innovatively identified by combining complete genome and LC-MS/MS. BMP11 was obtained by heterologous expression in E. coli. MICs of BMP11 against tested foodborne pathogens were 0.3–38.4 μg/mL. BMP11 killed pathogens by cell wall perforation and cell membrane permeabilization. BMP11 inhibited the growth of L. monocytogenes in milk.